An IoT Based Multi functional Robot for Military Applications - B, Arjun; Dr. Suresh D (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
In the recent development and trend most of the Defense organization now takes the help of robots to carry out many risky jobs that cannot be done by the soldier. These robots used in Defense are usually employed with the integrated system, including video screens, sensors, metal detector and cameras. The Defense robots also have different shapes according to the purposes of each robot. Here the new system is proposed with the help of wireless camera through we can trace out the intruders and the robot will be employed with integrated systems Thus the proposed system, a Multi-functional Robot using Internet of Things with wireless network GSM through which we can update the data to web page server and control remotely. This is specially designed robotic system to save human life and protect the country from enemies.